Real-world experience with Lenvatinib Plus Everolimus (LEN+EVE) in patients with pretreated advanced renal cell carcinoma (RELEVANCE): a retrospective, multicenter case series - Eggers, Hendrik; Stelmacher, Ramona; Bögemann, Martin; Strauß, Arne; Thomas, Christian; Landmesser, Johannes; Zschäbitz, Stefanie; Ivanyi, Philipp (Clinical genitourinary cancer, 2025)
Introduction - Metastatic renal cell carcinoma (mRCC) has a poor prognosis despite recent changes in systemic treatment options. Lenvatinib plus everolimus (LEN+EVE), a combination of 2 targeted therapies, is approved after failure of one prior tyrosine kinase inhibitor (TKI) therapy. Our objective was to evaluate the effectiveness and safety of LEN+EVE therapy in patients with mRCC in a real-world setting. - Patients and Methods - This retrospective case series included patients with mRCC treatment with LEN+EVE between August 2016 and December 2021 at 6 academic centers in Germany. Outcomes included overall survival (OS), progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and safety; all evaluated by local investigator. Subgroup analyses by risk scores, previous therapies, and initial dosing were performed. - Results - Eighty-one patients were assessed: median age was 61 years (range 42-80), 81.5% were men, and 80.2% of patients had an ECOG score of 0 or 1. Synchronous metastases were found in 39.5% of patients at initial diagnosis. The International Metastatic RCC Database Consortium (IMDC) risk status was favorable in 16.0%, intermediate in 48.1%, and poor in 16.0% of patients. The median number of treatment lines prior to LEN+EVE was 3 (range 0-7). Median treatment duration with LEN+EVE was 6.1 months (range 0.2-29.2). The ORR was 28.4%, DCR was 61.7%, median OS was 11.3 months (95% CI, 8.7-13.9), and median PFS was 6.5 months (95% CI, 5.4-7.6). Median PFS, OS and ORR were similar across patients with 0-2 versus ≥ 3 previous therapeutic lines and for patients with or without previous immunotherapy. The safety profile was manageable, with 6.2% of patients discontinuing treatment due to treatment-related adverse events. - Conclusions - LEN+EVE combination therapy demonstrated high effectiveness in heavily pre-treated, real-world cohort of patients with mRCC and challenging disease characteristics—regardless of treatment line, IMDC risk group, initial dosing, or previous treatment with immunotherapy.
Online verfügbar: 6. Oktober 2025, Artikelversion: 22. November 2025
Gesehen am 27.02.2026